Diffuse large B-cell lymphoma recurrence presenting as multiple, progressive cranial neuropathies - Goron, Abby R (BMJ Case Rep, 2019)
A 58-year-old man with a history of rheumatoid arthritis and stage IV diffuse large B-cell lymphoma, in complete remission with no evidence of residual disease on positron emission tomography/CT after completing six cycles of rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone chemotherapy, presented with acute onset of dysphagia to solids and liquids. On further evaluation, his dysphagia was attributed to a vagus nerve palsy, and later during his admission, he developed rapidly progressing left facial and vestibulocochlear nerve palsies. Imaging studies displayed pathological enhancement of bilateral seventh and eighth cranial nerves, concerning for leptomeningeal recurrence of lymphoma. Cerebrospinal fluid analysis and flow cytometry were confirmatory, revealing markedly atypical monotypic CD19 positive B cells.